2021
DOI: 10.1038/s41598-021-02124-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phenotypic change in a polymorphic salamander over 43 years

Abstract: Color polymorphic animals offer a unique system for studying intraspecific phenotypic responses to climate change. Discrete color morphs are easy to identify, and correlated trait responses of morphs can indicate how climate warming may facilitate long-term maintenance of polymorphisms. We use a historical dataset spanning 43 years to examine temporal shifts in color morph frequency and body size in response to climate in the Eastern Red-backed Salamander, Plethodon cinereus, which contains a widespread stripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…Our finding of a positive relationship between elevation and striped morph frequency is consistent with previous studies ( Gibbs and Karraker, 2006 ; Moore and Ouellet, 2015 ; Hantak et al., 2021 ). Following the expectation that higher elevations are typically colder than lower elevations, we predicted the observed positive correlation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of a positive relationship between elevation and striped morph frequency is consistent with previous studies ( Gibbs and Karraker, 2006 ; Moore and Ouellet, 2015 ; Hantak et al., 2021 ). Following the expectation that higher elevations are typically colder than lower elevations, we predicted the observed positive correlation.…”
Section: Discussionsupporting
confidence: 93%
“…However, here and in other studies, striped morphs are not always associated with cooler temperatures. A recent study by Hantak et al. (2021) found the proportion of striped morphs increases with increasing elevation and mean annual temperature and, based on these results suggested that these predictors may be decoupled in relation to color morph frequency in P. cinereus .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, here and in other studies, striped morphs are not always associated with cooler temperatures. A recent study by Hantak et al (2021) found the proportion of striped morphs increases with increasing elevation and mean annual temperature and, based on these results suggested that these predictors may be decoupled in relation to color morph frequency in P. cinereus . While the reason for greater proportion of striped morphs in higher elevations remains unclear, it may be possible that gene flow is reduced along altitudinal gradients in this species.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, some studies have found no climate-related morph trends or inconsistent patterns over time (Petruzzi et al, 2006;Muñoz et al, 2016;Evans et al, 2018). Fisher-Reid et al (2013 demonstrated that striped morphs were found in warmer, wetter habitats on Long Island, New York, while Hantak et al (2021) found striped morphs were more associated with warmer, drier habitats in localities across Maryland, New York, and Virginia. Range-wide, dense data can help examine overall trends and localize those at finer scale in a unifying framework.…”
Section: Climate and Color Morph Trends In The Eastern Red-backed Sal...mentioning
confidence: 99%